The spitzer deep, wide-field survey - Ashby, M.; Stern, D.; Brodwin, M.; Griffith, R.; Eisenhardt, P.; Kozlowski, S.; Kochanek, C.; Bock, J.; Borys, C.; Brand, K.; Brown, M.; Cool, R.; et al. (Institute of Physics Publishing, 2009)
The Spitzer Deep, Wide-Field Survey (SDWFS) is a four-epoch infrared survey of 10 deg2 in the Boötes field of the NOAO Deep Wide-Field Survey using the IRAC instrument on the Spitzer Space Telescope. SDWFS, a Spitzer Cycle 4 Legacy project, occupies a unique position in the area-depth survey space defined by other Spitzer surveys. The four epochs that make up SDWFS permit - for the first time - the selection of infrared-variable and high proper motion objects over a wide field on timescales of years. Because of its large survey volume, SDWFS is sensitive to galaxies out to z ~ 3 with relatively little impact from cosmic variance for all but the richest systems. The SDWFS data sets will thus be especially useful for characterizing galaxy evolution beyond z ~ 1.5. This paper explains the SDWFS observing strategy and data processing, presents the SDWFS mosaics and source catalogs, and discusses some early scientific findings. The publicly released, full-depth catalogs contain 6.78, 5.23, 1.20, and 0.96 × 105 distinct sources detected to the average 5s, 4?-diameter, aperture-corrected limits of 19.77, 18.83, 16.50, and 15.82 Vega mag at 3.6, 4.5, 5.8, and 8.0µm, respectively. The SDWFS number counts and color-color distribution are consistent with other, earlier Spitzer surveys. At the 6 minute integration time of the SDWFS IRAC imaging, >50% of isolated Faint Images of the Radio Sky at Twenty cm radio sources and >80% of on-axis XBoötes sources are detected out to 8.0µm. Finally, we present the four highest proper motion IRAC-selected sources identified from the multi-epoch imaging, two of which are likely field brown dwarfs of mid-T spectral class. © 2009. The American Astronomical Society. All rights reserved.